Conditioned Media of Choroid Plexus Epithelium Cells Attenuates High Pi-Induced Calcification of MOVAS Cells by Inhibiting ROS-Mediated Signal Pathways - Hui, Xin; Wang, Mei; Zhang, Lijun; Liu, Ji; Wang, Mengen; Hu, Weiwei; Zhang, Tongtong; Zhao, Shijun; Geng, Shangyong; Wang, Xianjun; Zheng, Zuncheng (Frontiers in Physiology, 2021)
Vascular calcification was an independent risk of cardiovascular and cerebrovascular diseases (CCD). Studies reported that conditioned media of choroid plexus epithelium cells (CPECs-CM) showed potential neuroprotective effects. However, the protective effect of CPECs-CM against vascular calcification (VC) has not been reported yet. Herein, high phosphate (HPi)-induced calcification model in mouse aortic vascular smooth muscle cells (MOVAS) was established, and protective effects and underlying mechanism of CPECs-CM against HPi-induced calcification were explored. The results indicated that CPEC cells were successfully isolated and cultured, and CPECs-CM co-treatment significantly inhibited HPi-induced calcification of MOVAS cells through blocking alkaline phosphatase (ALP) activity and expression. CPECs-CM co-treatment also suppressed reactive oxide species (ROS)-mediated DNA damage in HPi-treated MOVAS cells. Moreover, dysfunction of MAPKs and PI3K/AKT pathways both contributed to HPi-induced calcification of MOVAS cells, and CPECs-CM co-treatment attenuated HPi-induced calcification by normalizing MAPKs and PI3K/AKT expression. Taken together, our findings provided evidences that CPECs-CM had the potential to inhibit vascular calcification with potent application in chemoprevention and chemotherapy of human CCD.